Analyzing Geothermal Heat Exchangers Using Comsol Non-Isothermal Pipe Flow Model - Mohammed A. Atiya; Ali Naser Hussien; Azher M. Abed; Philippe Mandin; Farkad Ali Lattieff (Al-Khwarizmi Engineering Journal, 2025)
Earth–air heat exchangers (EAHE) hold great promise for reducing typical air conditioning systems’ energy consumption whilst preserving high indoor comfort. The present analyses a 3D model using COMSOL Multiphysics software for a geothermal heat exchanger to examine the thermal behavior along the piping system. The experimental findings of the real EAHE in Baghdad City during January and June are transferred into the nonisothermal pipe flow interface for modeling temperature, velocity and pressure distributions along the piping system. The temperature variation of subsurface soil and the radial temperature distribution around the pipe are modeled into the heat transfer interface.  The magnitude of heat flux is also computed in different times along the pipe. The effects of the continuous operation of EAHE on the output temperature and on the soil temperature around the pipe are also considered. The model’s output demonstrates that the air temperature rise in January is 10 whereas the air temperature drop is 14  in June. The effect of extracted/absorbed heat transfer from/to air in pipes is extended up to 0.7 m in the radial direction of the soil surrounding pipes due to continuous airflow in EAHE.